Impact of diabetes on healthcare costs in a population‐based cohort: a cost analysis. Issue 3 (19th August 2015) - Rosella, L. C.; Lebenbaum, M.; Fitzpatrick, T.; O'Reilly, D.; Wang, J.; Booth, G. L.; Stukel, T. A.; Wodchis, W. P.
Abstract: Aims: To estimate the healthcare costs attributable to diabetes in Ontario, Canada using a propensity‐matched control design and health administrative data from the perspective of a single‐payer healthcare system. Methods: Incident diabetes cases among adults in Ontario were identified from the Ontario Diabetes Database between 2004 and 2012 and matched 1:3 to control subjects without diabetes identified in health administrative databases on the basis of sociodemographics and propensity score. Using a comprehensive source of administrative databases, direct per‐person costs (Canadian dollars 2012) were calculated. A cost analysis was performed to calculate the attributable costs of diabetes; i.e. the difference of costs between patients with diabetes and control subjects without diabetes. Results: The study sample included 699 042 incident diabetes cases. The costs attributable to diabetes were greatest in the year after diagnosis [C$3, 785 (95% CI 3708, 3862) per person for women and C$3, 826 (95% CI 3751, 3901) for men], increasing substantially for older age groups and patients who died during follow‐up. After accounting for baseline comorbidities, attributable costs were primarily incurred through inpatient acute hospitalizations, physician visits and prescription medications and assistive devices. Conclusions: The excess healthcare costs attributable to diabetes are substantial and pose a significant clinical and public health challenge. This burden is an important consideration for decision‐makers, particularly given increasing concern over the sustainability of the healthcare system, aging population structure and increasing prevalence of diabetic risk factors, such as obesity. What's new?: Using a validated, population‐based registry, we created the largest propensity‐matched cohort (almost 3 million people) to provide comprehensive and current estimates of the healthcare costs attributable to diabetes. The attributable costs were estimated using a newly developed person‐centred costing methodology, representing the most comprehensive healthcare costs published. Attributable costs were ˜C$10, 000 per‐person over the study follow‐up, with nearly C$4, 000 being spent during the year after diagnosis. The excess healthcare costs attributable to diabetes reported in this study could be useful for allocating resources for diabetes and for accurate inputs into economic evaluations of diabetes intervention and management.